Aṡar Ad Dīn Fī Tanmiyaħ Wa Tarsīkh Qīmaħ As Silmi Al Ijtimāī’: أثر الدين في تنمية وترسيخ قيمة السِّلم الاجتماعي - Balah, Abdel Rahman Elsayed Elsayed Abdel Ghaffar (Civilization Research: Journal of Islamic Studies, 2024)
The aim of the research is to clarify the concept of peace in Islam, and to define its importance and value in Islam, and that Islam is the religion of peace. The one based on adherence to Islamic values is the one that lasts for a long time, and the research is presented to show humanity’s need for the religion of Islam, and its impact on achieving, strengthening and consolidating the concepts of social peace, which is the prominent feature of this religion, as it regulates people’s lives, and is considered as a revelation that guides minds and thus achieves The integrity and stability of the human soul, as religion is one of the important and necessary aspects of human life and society, as it is the one that guarantees the achievement of justice and equality among people. The descriptive and analytical approaches are a way to achieve its goal, the research plan: the research is organized into an introduction, two sections, a conclusion, and recommendations. search.